The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12973/eu-jer.8.1.313
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biology Laboratory Practices Supported with Self-regulated Learning Strategies on Students' Self-directed Learning Readiness and Their Attitudes towards Science Experiments

Abstract: Self-regulation is an active and constructive process in which students regulate and observe their own behaviour, motivations and cognition by setting their own goals during their learning process. In this study, the aim is to investigate the effects of biology laboratory practices that are supported by self-regulated learning strategies on students' readiness for self-directed learning and their attitudes towards science experiments in laboratory settings. This study, which was undertaken as a quasiexperiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…These learners are capable of implementing cognitive learning strategies in academic tasks (Vrieling et al, 2012) and good at regulating learning to enhance their outcomes of learning (Steffens, 2006). Also, it is essential to highlight that increased use of learning strategies is followed by increased level of academic outcomes (Oflaz, 2019), and it is evidence that SRL leads to positive academic outcomes (Kayacan & Sonmez Ektem, 2019).…”
Section: Discussion Of Rq2 and Rq3 Resultsmentioning
confidence: 99%
“…These learners are capable of implementing cognitive learning strategies in academic tasks (Vrieling et al, 2012) and good at regulating learning to enhance their outcomes of learning (Steffens, 2006). Also, it is essential to highlight that increased use of learning strategies is followed by increased level of academic outcomes (Oflaz, 2019), and it is evidence that SRL leads to positive academic outcomes (Kayacan & Sonmez Ektem, 2019).…”
Section: Discussion Of Rq2 and Rq3 Resultsmentioning
confidence: 99%
“…Beberapa point penting yang diamati dalam pembelajaran yang didasarkan pada self directed learning, diantaranya; 1) ada proses yang berorientasi pada tujuan, yaitu, peserta didik memiliki tujuan, 2) peserta didik mengambil inisiatif sendiri dan melaksanakan tugasnya secara mandiri untuk mencapai tujuan, yang berarti sehingga akan muncul sikap bertanggung jawab, 3) peserta didik memiliki kesadaran metakognitif. (Kayacan & Ektem, 2019).…”
Section: Hasil Penelitian a Konsep Pembelajaran Self Directed Learningunclassified
“…Consequently, instructional management can stimulate the students to have belief, good feeling, and have an impressive experience with learning leading to cooperation and instructional achievement [22,23,24]. As a result, researchers often consider an attitude toward mathematics as a predictor of ongoing academic success [25]. The recent findings by Damrongpanit [20] showed that when teachers provide quality of learning experiences for good learners, namely 1) planning and preparing instruction, 2) promoting the environment and enhancing good relationship, 3) applying teaching strategies based on learner's experience, 4) apply appropriate media, technology for learning content and goals, and 5) use of the measurement and evaluation of learning to improve learners, good instructional management does not affect only mathematics achievement of the 9 th grade students, it also affects attitude toward mathematics, achievement motivation, and mathematics self-efficacy before affecting mathematics achievement.…”
Section: Factors Affecting Mathematics Achievement Of Studentsmentioning
confidence: 99%
“…The findings have consistency with Pitsia et al [19] that the relationship of all three factors affected mathematics achievement. For this reason, researchers in many disciplines consider applying an attitude to explain the effects on the learners in various knowledge and desirable behaviors for science reading [25], and perception of creative reading [26] and digital technology [27], etc.…”
Section: Factors Affecting Mathematics Achievement Of Studentsmentioning
confidence: 99%